Wittig Reactions of Maleimide-Derived Stabilized Ylides with Alkyl Pyruvates: Concise Approach to Methyl Ester of (±)-Chaetogline A - Shelar, Santosh V.; Argade, Narshinha P. (Synthesis, 2021)
A facile synthesis of methyl ester of chaetogline A is reported starting from the corresponding methyl 1-methyltryptophanate-derived maleimide. A stereoselective Wittig olefination with a carbonyl function in methyl pyruvate followed by phosphorous pentoxide-induced regioselective dehydrative cyclization are the essential reactions. An acid-induced thermodynamically driven stereoselective β- to α-position migration of the exocyclic C=C bond unit in ethyl tetrahydroindolizinoindolylidenepropanoate is described.
Keywords: natural product; chaetogline A; amino acid; maleimide; methyl pyruvate; Wittig reaction; dehydrative cyclization